2007
DOI: 10.4161/cbt.6.6.4195
|View full text |Cite
|
Sign up to set email alerts
|

XIAP is highly expressed in esophageal cancer and its downregulation by RNAi sensitizes esophageal carcinoma cell lines to chemotherapeutics

Abstract: X-linked inhibitor of apoptosis protein (XIAP) is the most potent member of the IAP gene family in terms of its ability to inhibit caspases and suppress apoptosis. In this study, we investigated the expression of XIAP in esophageal cancer tissues and cell lines, and found the elevated expression of XIAP in esophageal cancer tissues compared with normal tissues. Then we used small interfering RNA (siRNA) to block XIAP expression while evaluating the effect of XIAP siRNA on cell apoptosis, and the combined effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 26 publications
3
38
0
1
Order By: Relevance
“…XIAP siRNA enhances sensitivity to methotrexate in hepatoma (Chen et al, 2006), to cisplatin, fluorouracil and etoposide in oesophageal carcinoma (Zhang et al, 2007), to TRAIL in melanoma, breast cancer and pancreatic cancer (Chawla-Sarkar et al, 2004;McManus et al, 2004) and also sensitises pancreatic cancer cell lines to g-irradiation (Giagkousiklidis et al, 2007). The XIAP siRNA approach confirmed the validity of XIAP as a therapeutic target but the problem of in vivo delivery of siRNAs regimens still must be overcome.…”
Section: A549mentioning
confidence: 69%
“…XIAP siRNA enhances sensitivity to methotrexate in hepatoma (Chen et al, 2006), to cisplatin, fluorouracil and etoposide in oesophageal carcinoma (Zhang et al, 2007), to TRAIL in melanoma, breast cancer and pancreatic cancer (Chawla-Sarkar et al, 2004;McManus et al, 2004) and also sensitises pancreatic cancer cell lines to g-irradiation (Giagkousiklidis et al, 2007). The XIAP siRNA approach confirmed the validity of XIAP as a therapeutic target but the problem of in vivo delivery of siRNAs regimens still must be overcome.…”
Section: A549mentioning
confidence: 69%
“…Median expression of cIAP-1, cIAP-2 and survivin in the study group was 25.95% (range 0.2-79.1%), 16.7% (range 0.3-62.2%) and 4.6% (range 0-12.3%) respectively. These results were not significantly different compared to the control.…”
Section: Resultsmentioning
confidence: 99%
“…The association between upregulation of IAP family proteins, such as XIAP, cIAP-1, cIAP-2 and survivin, and an unfavorable course of disease has been confirmed in chronic lymphocytic leukemia [12]. Also, pathological overexpression of IAP family members has been observed in various solid tumors including prostate cancer, breast cancer, pancreatic cancer, gastric cancer and melanoma [13][14][15][16][17][18].…”
mentioning
confidence: 88%
“…Croci DO et al have shown that after siRNA transfection against survivin and down-regulation of survivin, translocation of the AIF from the cytoplasm to the nucleus occurs, which is a molecular indicator of the caspase-independent apoptosis of cells (Croci et al, 2008). Combined use of cisplatin, fluorouracil, paclitaxel, etoposide, and XIAP siRNA have been shown to result in better chemotherapeutic activity and to efficiently decrease XIAP expression and make it sensitive to cancer treatments (Zhang et al, 2007;Wei et al, 2008).…”
Section: Targeting Iapsmentioning
confidence: 99%